THE INFLUENCE OF COOPERATIVE GAMES FOR CHILDREN SOCIALISATION AT RISKIN SCHOOL SOCIAL PROFº NILTON BALIEIRO MACHADO. (Fiep Bulletin - online, 2014)
This study aimed to nurture the socialization of children at social risk through cooperative games . For this we used the method of action research is that the commitment of the research staff and involvement with the community declared in the practice of social group , through the field diary , participant observation and semi - structured interview . As a sample, we used 4 classes at school , with 2 of 5 and 2 ª serie 6th series , 5 questions were asked with 4 to 7 students from 5th series and 3 in the 6th grade. The action research aimed to observe how they can socialize children at social risk in Physical Education classes through cooperative games. After collecting the data we can see how important cooperative content in physical education classes games is, once the socialization of children with difficulties working group thus achieving the main objective of this research occurred.
Keywords: Socialization; Social Risk Cooperative Games; Physical Education